Night the rich men burned - Mackay, Malcolm, 1982- (Mulholland Books/Little, Brown and Company, 2016)
"Oliver Peterkinney and Alex Glass, two friends from Glasgow's desperate fringes, become involved in one of the city's darkest and most dangerous trades: debt collection. While one rises quickly through the ranks, the other falls prey to the industry's addictive lifestyle, accumulating steep debts of his own. Meanwhile, the three most powerful rivals in the business--Marty Jones, ruthless pimp; Potty Cruickshank, member of the old guard; and Billy Patterson, brutal newcomer--vie for prominence. And now Peterkinney, young and darkly ambitious, is beginning to make himself known. Before long, violence will spill out onto the streets, as those at the top make deadly attempts to out-maneuver one another for a bigger share of the spoils. Peterkinney and Glass will find themselves at the very center of this war; as the pressure builds, each will find their actions--and inactions--coming back to haunt them. But it is those they love who will suffer most."--Publisher's description.